REVIEW ON HEALTH HAZARDS OF CELL PHONE RADIATION - A PROPHYLACTIC WARNING - SEKAR BABU HARIRAM; G.MURUGA BOOPATHY; S.THENESH KUMAR (International Journal of Pharma and Bio Sciences, 2013)
Cell phones have become very important communication tool for the reach of common person Now a situation has come that without cell phone one cannot be comfortable both in domestic and business circle. For the past 15 years scientist started working to screen the harmful effects of cell phone radiation. The resulting reports from the study are quite contradictory because majority of studies published have failed to show an association between exposure to radiofrequency [RF] from a cell phone and health problems. While RF energy doesn’t ionize particles, but large amounts can increase body temperatures and cause tissue damage. Two areas of the body, the eyes and the testes, are particularly vulnerable to RF heating because there is relatively little blood flow in them to carry away excess heat. Whereas other reports say that Cell phone users had an increased risk of malignant gliomas, acoustic neuromas. But recent reports enlighten that one hour of cell phone use per day significantly increases tumor risk after ten years or more. Further studies explain about the Gene -toxic effect, reduction in reproductive capacity in animal study. Whereas other report is quite encouraging to note that cell phone radiation has not disturbed sleep and cognitive functions. Since the results are quite contradictory, hence it is necessary to review the study related to electro magnetic effect of cell phone on human health to create awareness among the people to give more emphasis on limited use of cell phone to protect innocent future generation of India.